The influence of social support on academic performance: The mediating role of cognitive engagement - Achdiyah, Heni Nur; Latipun, Latipun; Yuniardi, Muhamad Salis (University of Muhammadiyah Malang, 2023)
Academic performance, which measures a student’s success in learning, is influenced by various factors. One of the most important determinants of academic performance is social support. Parents, teachers, and friends all play a critical role in providing the necessary support that affects students’ cognitive engagement. Therefore, this study aimed to determine the relationship between social support and academic performance, which could be directly or indirectly mediated by cognitive engagement. The subjects used were 228 high school students in 11th grade, aged 15-18. Data were measured using Academic Performance Rating Scale (APRS), Child and Adolescent Social Support Scale (CASS), and Students Engagement Scale (SES) with Cronbach’s alpha values of 0.84, 0.93, and 0.88, respectively. The mediation analysis was conducted using the PROCESS model 4 developed by Hayes. The results showed that the relationship between social support and academic performance occurred through the mediation of cognitive engagement (β = 0.16), with no direct correlation (β = 0.12, p = 0.350). Specifically, more excellent social support was associated with increased cognitive engagement (β = 0.50, p = 0.000), leading to improved academic performance (β = 0.32, p = 0.005). Therefore, it was confirmed that social support is essential to students’ cognitive engagement and academic performance.